Novel vaccination approaches against equine alphavirus encephalitides - Carossino, Mariano (2014)
The current production of inactivated vaccines for the prevention of equine alphavirus encephalitides caused by Eastern, Western and Venezuelan Equine Encephalitis viruses (EEEV, WEEV, VEEV) involves the manipulation of large quantities of infectious viral particles under biosafety level 3 containment laboratories with the potential risk of transmission to the operators. Moreover, these vaccines are not capable of inducing a long-lasting immunity. Modified live vaccines, which were also attempted, maintain residual virulence and neurotropism, causing disease in both horses and humans. Therefore, the production of an efficacious second generation vaccine which could be used in the prevention of alphavirus infection without the need to manipulate infectious viral particles under high biocontainment conditions could be of great benefit for the worldwide horse industry. Furthermore, equine alphaviruses are considered as biological threat agents. Subunit, chimeric, gene-deleted live mutants, DNA and adenovirus-vectored alphavirus vaccines have been evaluated; such approaches are reviewed in this work. Climate changes, together with modifications in bird and vector ecology, are leading to the arise of emerging pathogens in new geographical locations, and these zoonotic New World arboviruses are gaining concern. Novel vaccine development does show a promising future for prevention of these infections in both horses and humans.